On the Unification of Megamodels - Hebig, Regina; Seibel, Andreas; Giese, Holger (Electronic Communications of the EASST, 2012)
Through the more and more widespread application of model-driven engineering (MDE) and the increasing diversity in applied modeling paradigms within single projects, there is an increasing need to capture not only models in isolation but also their relations. This paper is a survey on techniques capturing such relations, such as megamodels or macromodels, based on existing scientific literature. Therefore, we consider various definitions of these techniques. We further examine characteristics of the different techniques. We will propose a unified core definition of a megamodel that captures the core properties of megamodels and which can be extended to the needs of the different applications of megamodels. Finally, we give an outlook on arising application areas for megamodels.